KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SESUAI DENGAN GENDER DALAM PEMECAHAN MASALAH PADA MATERI BALOK DAN KUBUS (STUDI KASUS PADA SISWA SMP KELAS VIII SMP ISLAM AL-AZHAR 29 SEMARANG) - Imam Wijaya, Henry Putra; Sujadi, Imam; Riyadi, Riyadi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of this research was to analyze the ability of mathematical communication in solving the problem of cube and cuboid material among male and female students in grade VIII of Islam Junior High School 29 Al-Azhar Semarang. This research was a qualitative research using case studies approach and used purposive sampling techniques to select the subjects of the study. The subjects were 4 students namely 2 male and 2 female students. The technique of data collection was conducted by reviewing documents and archives, conducting written tests and interviews. This study used triangulation time to validate the data. The data analysis techniques used in this research were data reduction, data presentation, and conclusion. The results showed that: (1) male students: (a) could express, demonstrate, and deliver their mathematical ideas visually, understand and interpret their mathematical ideas in writen or other visual forms, were able to convey the matemathical terms, notations, and its structures, were able to make connections between their ideas and the problem situation in writen form, (b) were able to express, demonstrate, convey, understand, interpret, and evaluate mathematical ideas; able to use the mathematical terms, notations and its structures; were able to convey their ideas using mathematical terms, notations of mathematics and its structures; were able to convey ideas and the relation between models of the situation in spoken form. (2) female students: had the same ability with male students, but they could evaluate their mathematical ideas in writing or in visual forms in the mathematical written communication.Key words: Mathematical Communication, Problem Solving, Gender